Occurrence and Pathogenicity of Root-Knot Nematodes (Meloidogyne species) in South African Vineyards - Loubser, J.T. (South African Journal of Enology and Viticulture, 2017)
The occurrence of root-knot nematodes (Meloidogyne species) in viticultural regions of South Africa was determined. Meloidogyne javanica constituted 73,2% of all species identified while M. arenaria (17 ,0% ), M. incognito (7 ,1 % ) and M. hap/a (2,7%) were also found. The relative frequency of species in the various regions differed widely, with M. incognito more prominent in the warm inland regions. Experiments on different rootstock cultivars showed that all four species were able to infest susceptible rootstocks while none of them could infest cultivars known to be resistant to root-knot nematodes. Meloidogyne incognito and M. javanica, however, were found to be more pathogenic than the other two species. Meloidogyne incognito also showed a higher pathogenicity at 33°C than M. javanica, while results demonstrated a breakdown ofrootstock resistance at this temperature. It could not be verified by short-term pot trials that a sandy soil type enhance the degree of root-knot nematode infestation.